Exploratory Study on ERM Disclosure Among Mesdaq Companies in Malaysia - Mohd Farid, Ibrahim (2009)
The objective of this study is to identify the reasons for the companies that listed in MESDAQ Market in Bursa Malaysia regarding ERM (Enterprise Risk Management) disclosure. The purpose is to know the factors that influence company decision to adopt ERM. The studied factors are using the numbers board of director and its category, types of audit firm, audit committee and its category, internal audit and duality factor. This study used data from 102 MESDAQ companies for the year 2006 to determine types of disclosure regarding ERM whether voluntarily, in extent disclosure or non-disclosure.